Knowledge co-creation in participatory policy and practice: Building community through data-driven direct democracy. Issue 1 (May 2021) - Godinho, Myron A; Borda, Ann; Kariotis, Timothy; Molnar, Andreea; Kostkova, Patty; Liaw, Siaw-Teng
Engaging citizens with digital technology to co-create data, information and knowledge has widely become an important strategy for informing the policy response to COVID-19 and the 'infodemic' of misinformation in cyberspace. This move towards digital citizen participation aligns well with the United Nations' agenda to encourage the use of digital tools to enable data-driven, direct democracy. From data capture to information generation, and knowledge co-creation, every stage of the data lifecycle bears important considerations to inform policy and practice. Drawing on evidence of participatory policy and practice during COVID-19, we outline a framework for citizen 'e-participation' in knowledge co-creation across every stage of the policy cycle. We explore how coupling the generation of information with that of social capital can provide opportunities to collectively build trust in institutions, accelerate recovery and facilitate the 'e-society'. We outline the key aspects of realising this vision of data-driven direct democracy by discussing several examples. Sustaining participatory knowledge co-creation beyond COVID-19 requires that local organisations and institutions (e.g. academia, health and welfare, government, business) incorporate adaptive learning mechanisms into their operational and governance structures, their integrated service models, as well as employing emerging social innovations.